Influencia de la televisión en la opinión de los ciudadanos estadounidenses durante la Guerra de Vietnam - Camacho González, Carolina (2018)
The following research aims to provide an analysis of how the evolution of broadcast news about the Vietnam War influenced the public opinion of US citizens. It is based on different surveys and an analysis of the television reports from ABC, CBS and NBS telecasted between 1967 and 1971.The period of time analyzed for the present work is between 1967 and 1971. During those years, television began to play a major role and had influence on US citizens. Hence television was the main source of information about what was going on around the world and it changed the way channels reported what was happening in Vietnam showing images and videos on site which carried the war to American homes. The results of the investigation show that there was a correlation between the televised broadcasts about the Vietnam War and the changeover public opinion of US citizens. Hence at the time the on-site transmissions were increased there was a variation in public opinion started towards a more negative view of the War.